The Understanding of Javanese Ethnic Local Wisdom in Serat Panitisastra and Its Utilization as Moral Education - Amurwa Pradnya Sang Indraswari (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2017)
Javanese ethnic local wisdom of moral and manners teachings include in Serat Panitisastra.The local wisdom is evolving among community through Serat Panitisastraliterary works which contain moral precepts. Serat panitisastra comprising 10 pupuh tembang where its oral tradition is chanting some songs or tembang which contains moral teachings, then it can be easily remembered and applied in the life of society. The javanese ethnic local wisdom is included in Serat Panitisastra. The message from serat writer is piwulangor moral teaching, for instance teaching about good and bad of things, social care, good manners, respect for older people, friends and teachers. In this modern era, moral teaching through the understanding of serat panitisastra which has been carried out by Javanese ethnic should be utilised in Indonesia moral education.